Accelerate Mass Transport of Proton and Carbon Sources by Super‐Hygroscopic and Porous Nanosheets for Continuous CO2‐To‐Ethylene Upgrade - Silong Dong; Guobin Wen; Xinyu Yang; Xiaowen Zhang; Shuxuan Liu; Haoyang Xiong; Yinyi Liu; Kai Zong; Hao Li; Yifan Li; Yi Cui; Bohua Ren; et al. (Advanced Science)
Abstract Gas‐water/catalyst triple‐phase interface and the microenvironment play critical roles in the reaction kinetics and production rate of electrochemical carbon dioxide reduction reactions (CO2RR), which steer concerted proton‐electron transfer steps. Inspired by Tillandsia leaves, which efficiently capture H2O and CO2 from the air, copper nanosheets with dual‐functional channels are we designed: the superhygroscopic network enables capillary condensation, converting H2O(g) into H2O(l) to form H2O channels that ensure a stable supply of protons, while the CO2 channels formed by the microporous structure enhance the diffusion of CO2, thus enriching the carbon source. This synergistic design creates an optimal microenvironment for CO2 conversion by simultaneously delivering both protons and CO2 to the reaction interface. Time‐of‐flight secondary‐ion mass spectroscopy (TOF‐SIMS), X‐ray absorption spectroscopy (XAS) and multiphysics simulations further reveal the designed H2O and CO2 channels in the microenvironment to boost mass transports. Hence, the Faradaic efficiency (FE) for ethylene reaches up to 96% at ‐200 mA cm−2 with such localized triple‐phase interfaces, which simultaneously exhibits ultra‐high stability for over 170 h in the membrane electrode assembly (MEA) system. This strategy provides a construction methodology of H2O and CO2 channels for improving the selectivity and stability of electrochemical CO2 upgrades.